PRAWO W MEDYCYNIEMedical staff’s observance of patient’s right to privacy while undergoing medical procedures - Wroński, Konrad; Cywiński, Jarosław; Depta, Adam; Bocian, Roman; Dziki, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: One of the basic rights of a patient is the right to privacy while undergoing treatment from the medical staff. The doctor providing medical services should pay special attention to patients’ privacy. For every patient privacy is a very sensitive, confidential and individual aspect of life. Aim: The objective of this research was to evaluate to what extent a patient’s right to privacy is respected while he/she undergoes medical procedures. Material and Methods: A group of 250 patients treated in Wojewódzki Specjalistyczny Szpital im. dr Mikołaja Pirogowa in Łódź was interviewed by means of the author’s own survey designed so as to assess the exercising of the patient’s right to privacy while receiving treatment. The necessary statistics were conducted by means of STATISTICA 7.1 and EXCEL 2008 programs. Results: The analysis of the results shows that only 65 (26%) patients considered that a patient’s right to privacy while undergoing medical procedures was not respected. 185 (74%) of the respondents were of a different opinion. Conclusions: The right to privacy while undergoing medical procedures is one of the basic patient’s rights. Medical staff must respect this right. People who contravene the right to privacy during hospital stay are exposed to sanctions set down in the civil code.